Towards effective subject leadership in the primary school - Bell, Derek; Ritchie, Ron. (Buckingham : Open University Press, 1999)
Changing responsibilities and roles. Teaching and learning. Working with colleagues. Resources. Contributing to school improvement.
Keywords: Education; Elementary school teaching; Master teachers; Master teachers -- Great Britain; Mentoring in education -- Great Britain; Teacher participation in curriculum planning -- Great Britain; Elementary school teaching -- Great Britain